The impact of physical activity on students' happiness in the context of positive and negative motivation - Katarzyna Blonska (Physical Education of Students)
Background and Study Aim. This study investigated whether the physical activity and the type of motivation among students inactive in professional sport can enhance their life satisfaction. Material and Methods. An experimental study was conducted with the participation of 164 students (not athletes) aged 24,52±4.  In the experimental groups participants engaged in physical activity which they performed at their leisure 3 times a week for at least 30 minutes for 6 weeks. Additionally, the students were motivated to be active in a positive way (focus on benefits), in a negative way (focus on avoiding losses) or were not motivated at all. The experiment was based on a mixed group plan - with the initial and final measurement of the Satisfaction With Life Scale (SWLS), Positive and Negative Affect Schedule (PANAS).